Eating behavior and health-related quality of life among female students attending higher education during COVID-19 pandemic in Indonesia - Dian Novrianti; Dian Novita Chandra; Judhiastuty Februhartany (World Nutrition Journal, 2023)
Background: Female students attending higher education had lower Health-related Quality of Life (HRQOL) scores and their eating behavior, which is a key element of healthy lifestyle, had changed to become unhealthy as a result of the pandemic's mental effects. There has been no study assessing the asssociation between both during the pandemic in Indonesia, especially after controlling for other factors. Objective : This study aimed to assess the association between eating behavior and HRQOL among female students attending higher education during Covid-19 Pandemic. Methods: This was a cross-sectional online survey with 474 subjects aged 18 to 25. The Dutch Eating Behavior Questionnaire (DEBQ) was used to assess emotional, external, and restraint eating. HRQOL was measured using the SF-36 questionnaire, with the subscales Physical Component Summary (PCS) and Mental Component Summary (MCS). Additionally, sociodemographic data, screen time, sleep duration, nutritional status, and physical activity were collected. The data were analyzed using multiple linear regression. Results: PCS was significantly associated with emotional eating (r = 0.279, p-value <0.001), external eating (r = 0.211, p-value <0.001), and restrain eating (r = 0.116, p-value = 0.012). Besides, emotional eating (r = 0.211, p-value <0.001) and external eating (r = 0.172, p-value <0.001) were also significantly associated with MCS score Conclusion: During Covid-19 pandemic, the higher the emotional, external, and restraint eating behavior scores of the students, the higher their physical health-related quality of life. The higher the emotional and external eating behavior scores, the higher their mental health-related quality of life.